RAQAMLI DAVRDA BOLALAR ADABIYOTI: ELEKTRON VA AUDIO KITOBLARNING O‘RNI - Normurodovа Nigorа; Radjabova Nargis (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the impact of digital technology development on children's literature, the importance of electronic and audiobooks in the educational process, and their role in shaping reading culture. In addition, several problematic aspects of the topic are also discussed.